2000
DOI: 10.1089/neu.2000.17.53
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasma Magnesium Concentration and Oxidative Stress Following Graded Traumatic Brain Injury in Humans

Abstract: Plasma magnesium, calcium, and oxidative status were investigated in 31 male casualties with traumatic brain injury (TBI) during a 7-day posttraumatic period. The study group consisted of eight patients with mild closed head injury (Glasgow Coma Scale score [GCS] of 13-15), 10 patients with extensive penetrating head injury (GCS 4-6), and 13 patients with blast injuries but without direct head trauma. The latter group was included since previous experimental and clinical data have confirmed the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 74 publications
4
63
0
3
Order By: Relevance
“…Significant declines in blood free magnesium concentration have been reported following both direct (97) and indirect clinical neurotrauma (98). These data show that both direct and indirect neurotrauma cause significant changes in divalent cation balance, and that following indirect neurotrauma, these changes are correlated to alterations in oxidative status/antioxidant defense.…”
Section: Clinical Studiesmentioning
confidence: 64%
“…Significant declines in blood free magnesium concentration have been reported following both direct (97) and indirect clinical neurotrauma (98). These data show that both direct and indirect neurotrauma cause significant changes in divalent cation balance, and that following indirect neurotrauma, these changes are correlated to alterations in oxidative status/antioxidant defense.…”
Section: Clinical Studiesmentioning
confidence: 64%
“…50 In humans with graded TBI with GCS scores of 4 -6 (extensive, penetrating injury) and 13-15 (mild, closed injury), a time-dependent increase of plasma ionized magnesium was observed for 7 days. 27 There was a persistent production of reactive oxygen species malondialdehyde and a delayed decrease of the antioxidant superoxide dismutase, suggesting increased antioxidant utilization. The study showed a correlation between the decline in plasma ionized magnesium concentration and the development of oxidative stress in TBI.…”
Section: Magnesium In Humans With Traumatic Brain Injurymentioning
confidence: 97%
“…26 These findings were confirmed in TBI patients: administration of magnesium sulfate reduced oxidative stress after TBI in humans. 27 In patients with subarachnoid hemorrhage undergoing temporary cerebral artery occlusion for clipping of cerebral aneurysm, treatment with magnesium sulfate dilated the leptomeningeal arteries and enhanced collateral blood flow and tissue oxygenation. 28 Molecular mechanisms have been studied on the efficacy of magnesium in attenuating the neurological damage in TBI.…”
Section: Mechanisms Of Neuroprotective Action Of Magnesiummentioning
confidence: 99%
See 1 more Smart Citation
“…26 The ROS are highly reactive molecules that contain an unpaired electron in the outermost orbit, increasing their potential for chemical reactivity. 27 As normal by-products of oxidative metabolism, these ROS, or free radicals, are constantly produced, but their concentration is usually tightly controlled by endogenous antioxidant mechanisms.…”
Section: Mitochondriamentioning
confidence: 99%